Principal Academic Supervision and Work Motivation and its Effect on Teacher Teaching Performance - Supriadi, Andri; Tamam, Badrud; Nurbaeti, Nurbaeti (Universitas Wiralodra, 2021)
Abstract-This is focused on the problem of the performance of teachers teaching caused by the lack of effective supervision of principal academic and Teacher work motivation. The purpose of this study is to measure the influence of principal academic supervision and teacher work motivation on teacher teaching performance. Research method: descriptive analysis, quantitative approach, analysis technique using product moment correlation, determination and regression using correlational and regression techniques. Data collection of questionnaire. The population of this study are teachers, while the unit of analysis using sampling is done by using cluster random sampling technique. The result of data analysis found that the principal academic supervision on teachers' teaching performance was positively correlated. Teacher's motivation to teacher's performance is positively correlated. Similarly, principal academic supervision and teacher work motivation on teacher teaching performance simultaneously have a strong positive correlation. In the regression equation in this study marked positive, this indicates a positive influence, meaning that if there is a change of one unit of academic supervision supervisor and teacher work motivation, it will be followed by changes in teacher teaching performance. In conclusion, there is a significant influence of principal academic supervision and teacher work motivation on teacher teaching performance. From the results of these studies, the authors suggest: increasing teacher work motivation can be done through clinical supervision by conducting class visits, individual talks and group discussions to discuss problems faced by the teacher. Providing regular guidance to conduct self-evaluation in providing lessons to students. Verbal rewarding for supervised teacher achievement.